Effect of Polymer Additives on Improvement of Concrete Properties - Neila Ye. Bekturganova; Inna V. Kolesnikova (Advances in Polymer Technology)
This article presents a review of achievements in the research aimed at improving the main building material—concrete—along with its physical, mechanical, and operational properties. As is well known, in the near future, the role of concrete will continue to be primary in the construction of buildings and structures due to increasing demand. However, despite its advantages, this important building material is not without flaws. In particular, due to its porosity, concrete is highly permeable to liquids, making it insufficiently resistant to frost and corrosion and sometimes even brittle. At the same time, concrete mixtures used in modern construction must meet requirements such as good adhesive properties, improved waterproofing, high workability, retention of rheological characteristics over time, and the potential for increased strength. Today, the use of polymer additives as modifiers to improving concrete is particularly relevant. The purpose of this review is to examine recent advances in understanding the impact of polymer additives of both inorganic and organic nature on improving concrete properties. Continued research in the field of polymer modifiers and exploration of new research opportunities are for engineering advancements and the development of modern materials.